PWE-186 iScan in the evaluation of small colonic polyps: outcomes, learning curve from a large propective series. (28th May 2012) - Basford, P J; Longcroft-Wheaton, G R; Bhandari, P
Abstract : Introduction: Indigocarmine (IC) and narrow-band imaging have been shown to be effective in the in vivo diagnosis of small colonic polyps. The learning curve for achieving high level of accuracy with a new technology for real-time diagnosis of small colonic polyps has not been determined. Methods: We aimed to assess the learning curve of a novel electronic in vivo diagnosis technology (Pentax iScan) for an expert endoscopist. Patients presenting for screening colonoscopy through the UK Bowel Cancer Screening Programme were prospectively recruited. All colonoscopies were performed by a single expert endoscopist, with extensive experience in in vivo diagnosis, using Pentax EC-3890Li 1.2 Megapixel HD colonoscopes and EPKi processor. Polyps <10 mm in size were assessed sequentially using three modalities (1) White light HD endoscopy (WL), (2) Pentax iScan surface and tone enhancement, (3) IC chromoendoscopy. Optical magnification was not used. Predicted histology (non-neoplastic, adenoma, cancer) was recorded for each modality and compared to the final histopathological diagnosis. Results were analysed for sensitivity and specificity for neoplasia, and overall accuracy. To assess any learning effect results were analysed in three sets of 100 consecutive polyps. Results: A total of 309 polyps were eligible for inclusion in the study. Mean polyp diameter was 4.1 mm, median 3 mm. 133 polyps were in the proximal colon and 176 in the distal colon. 109 polyps were non-neoplastic, 199 were adenomatous and one contained adenocarcinoma. Sensitivity and overall accuracy improved significantly for all three imaging modalities in the 3rd set of polyps as compared to sets 1 and 2 (p<0.05). In Set 3 overall accuracies of 92.7%, 93.6% and 93.6% were achieved with WL, iScan and IC respectively. There were no significant differences in overall accuracy between the three modalities in Set 3. Negative predictive values for adenomatous histology of recto-sigmoid polyps ≤5 mm for the entire study were 96.5%, 93.4% and 98.3% for WL, iScan and IC respectively. Conclusion: (1) Even in expert hands there is a significant learning curve for using a new technology for the in vivo diagnosis of small colonic polyps, with improvement in performance over the first 200 polyps assessed. (2) Excellent results can be achieved once the new technology has been mastered. (3) This is the first report of results achieved with high-definition white light endoscopy which are comparable with electronic chromoendoscopy and IC chromoendoscopy. Competing interests: None declared.